An analysis of flood activity over the past century based on the sedimentary deposits in the Mfolozi floodplain - Mbao, Chabala (Rhodes University, Faculty of Science, Department of Geography, 2017)
Floods are natural phenomena that are of widespread interest to the scientific community, particularly in the context of understanding the impact of climate change as well as changing land use patterns and the security of infrastructure such as towns and roads. In northern KwaZulu-Natal, large flood events have been a reoccurring feature over the past century. The geographical position and extent of the region means that is affected by both inland and coastal weather phenomena, each with the potential to cause large flood events. While information pertaining to large floods in the region in the form of flow data is readily available, flow data is often incomplete and limited in terms of how far back in time the records extend. The Mfolozi River floodplain itself also houses a record of flood activity in the region in the form of sedimentary deposits, which have the potential to reveal flood activity over a much longer timescale, even when monitoring of flood activity in the region was not present. Establishing a link between the hydrological and sedimentary features of floods may be useful in establishing a record of flood activity extending beyond the limits of historical records. The aim of this project was to construct a record of major flood events on the Mfolozi River floodplain over the last century and determine their source. The first objective involved establishing the history of flood events in the Mfolozi River catchment utilising hydrological data recorded throughout the catchment. Thirty nine different large floods (defined as being over 800 m3.s-1) were recorded on the floodplain over the past century. The data also highlighted differences in the extent of known coastal and inland systems (tropical cyclones and cut-off lows respectively), allowing for inferences to be made about the area of the catchment most likely affected by each event; some flood events were identified as having mostly affected the upper reaches of the catchment, while others mostly affected the lower reaches, closer to the coast. The second objective was to identify the various physical, mineralogical and geochemical features of the sediment deposited on the Mfolozi floodplain. Multiple individual flood deposits were identified in the sedimentary record, with sediment tracing analysis providing insight into the source of the deposits within the catchment; no traces of igneous or metamorphic material could be found within the sediment. The source rocks were identified as mostly quartzite, with minor shale and sandstone deposits as well. This put the source of the sediment in the upper to middle reaches of the catchment. The sedimentary analysis was combined with the hydrological records to establish a chronology of flood events extending back to the 1960's. Unfortunately, this record could not be extended further due to the limited amount of sediment collected as well the limits of readily available analytical techniques; radionuclide dating methods were unsuccessful due to the low amounts of fallout radionuclides present in the sediment. The study has however successfully established a history of flood events in the region, as well as providing a link between the hydrological and sedimentary features of flood events that could potentially be useful for current and future research.
Keywords: Floodplain morphology -- South Africa -- Mfolozi River; Floodplains -- South Africa -- Kwazulu-Natal; Sedimentation and deposition -- South Africa -- Kwazulu-Natal; Floods -- South Africa -- Kwazulu-Natal -- Measurement; Hydrology -- Research -- South Africa -- Kwazulu-Natal; Stream measurements -- South Africa -- Kwazulu-Natal